Disaster management effort in peatland and coastal areas through cross sectoral collaboration, case study in Bukit Batu District, Bengkalis Regency, Riau Province. Issue 1 (1st February 2022) - Purwanto, W; Hidayat, R; Ajar, S B
Abstract: This paper describes the disasters that occur in peatland and coastal areas, especially in Bukit Batu District, Bengkalis Regency, Riau Province. In addition, it is also explained about disaster management with cross – sectoral cooperation in accordance with the role of each sector so as to reduce the impact and even overcome the disaster. In this research paper using qualitative research methods and conducted with open interviews and filed surveys. As a result, with this cross-sectoral collaboration, land and forest has stoppes and the abrasion on the coast of Pangkalan Jambi Village has stopped and has even begun to form new land.